AB0751 Successfull maintenance treatment of granulomatous polyangiitis (wegener) with rituximab - a case series. (23rd January 2014) - Knight, A.; Hallenberg, H.; Baecklund, E.
Abstract : Background: Granulomatous polyangiitis (GPA) is a chronic relapsing systemic vasculitis and repeated remission treatment with cyclophosphamide poses long term safety risks. Studies of rituximab (RTX) have reported successful remission in patients with severe and relapsing GPA, however relapses continue to occur in more than half the patients (1, 2). Information about repeated RTX therapy in GPA is limited. Objectives: To evaluate the efficacy and tolerance of repeated RTX infusions in patients with relapsing GPA, previously treated with cyclophosphamide and other conventional immunosuppressants. Methods: A retrospective study of the clinical characteristics, previous treatments, disease activity, relapses and tolerance of RTX in GPA patients who had received RTX as maintenance treatment at our department between 2003 and 2011. Patients had to fulfill ACR and/or CHCC criteria for GPA. Disease activity was measured using BVAS. All patients were followed until Dec 31, 2011. Results: In total eleven patients with repeated RTX infusions were identified, six men and five women, all PR3 ANCA-positive. The patients had previously received a mean of 5, 6 different immunosuppressants, including cyclophosphamide and steroids. The mean cumulative dose of cyclophosphamide before RTX treatment was 50 g (range 11-105) and the median number of relapses were 3 (range 1-8). The patients have received a median of four (range 2 -11) maintenance RTX infusions (1000 mg x 2) every six months, with a median follow-up of 18 months from the first infusion (range 9-96). During follow-up no relapses have occurred and BVAS (median) dropped from 9 (range 15-4) before first infusion to 0 (range 2-0) after last infusion. 7 of 11 patients were in remission on Dec 31 2011, defined as BVAS=0 and prednisolone < =7, 5 mg. Three patients have stopped all concomitant immunosuppressant treatment. Seven infusion reactions have been noted (in three patients), all could continue treatment. Infections were the most frequently reported adverse events; the majority being "common colds", but seven infections needed treatment with antibiotics and one case of Pneumocystis jiroveci was recorded. Conclusions: Rituximab as maintenance treatment in this setting of GPA patients, with a median follow-up time of 18 months and receiving a median of four RTX treatments prevented further relapses, gave a good disease control and enabled reduction of steroids and other immunosuppressants. Rituximab was well tolerated but infections may prove an issue. References: N Engl J Med 2010;363:221-32 2. AnnRheumDis 2011Oct. e-pub) Disclosure of Interest: None Declared